Photographic record of Temminck’s Tragopan Tragopan temminckii (Gray, 1831) (Aves: Galliformes: Phasianidae) from eastern Bhutan: an evidence of its westward range expansion - Dorji, Tshering; Kinley, Kinley; Letro, Letro; Tshering, Dawa; Maidali, Prem Nanda (Journal of threatened taxa, 2021)
We report the second photographic evidence of Temminck’s Tragopan Tragopan temminckii from Bhutan.  Inhabiting warm broadleaved forest at an elevation of 2,952m, the species photo captured in a camera trap was much westward than its previous record, indicating westward range expansion of this rare and elusive bird.